Immunopathological effect of mercury on humoral immune response in chickens - Kumar, Avadhesh; Chauhan, R S; Singh, N P (The Indian Journal of Animal Sciences, 2012)
Effect of mercury on Ranikhet disease vaccine-induced humoral immune response was investigated in 80 chickens for 12 weeks. The experimental chickens were divided into two groups of 40 each. Group 1 was kept as control while in group 2, mercuric chloride was given @ 125 ppm daily for 12 weeks in drinking water. The humoral immune response was assessed by ELISA, haemagglutination inhibition test and P- lymphocyte blastogenesis assay at 2-week-interval by taking blood samples of 5 birds from each group. The humoral immune response including antibody titre against Ranikhet disease vaccine and P- lymphocyte blastogenesis were found to be decreased significantly (P